2013
DOI: 10.14742/ajet.270
|View full text |Cite
|
Sign up to set email alerts
|

Students' engagement with Facebook in a university undergraduate policing unit

Abstract: <p>Web 2.0 technologies are increasingly being used to support teaching in higher education courses. However, preliminary research has shown that students are using such technologies primarily for social purposes, rather than as a means of further engaging with academic content. This study examines a cohort of tertiary students' use of a Facebook page, which was created for a second year university policing unit at the Queensland University of Technology in Brisbane, Australia. Results from content analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…In a similar vein, several authors reported that the use of Facebook as an LMS had the potential to engage students even in out‐of‐class discussion with instructors and to increase student motivation, peer learning and feedback (Albayrak & Yildirim, ; Bariş & Tosun, ; Geyer, ; Karal et al, ; Miron & Ravid, ; Musa et al, ; O'Bannon, Beard, & Britt, ; O'Bannon, Britt, & Beard, ; Omar, Embi, & Yunus, ; Öztürk, ; Rachtam, Kaewkitipong, & Firpo, ; Rubrico & Hashim, ; Shih, ; Shraim, ; Souleles, ; Staines & Lauchs, ; Stankov, Glavinić, & Krpan, ; Varol, ; Vincent & Weber, ; Wang, Leng, & Lee, ).…”
Section: Formal Use Of Facebook In Formal Settings Of Learningmentioning
confidence: 98%
“…In a similar vein, several authors reported that the use of Facebook as an LMS had the potential to engage students even in out‐of‐class discussion with instructors and to increase student motivation, peer learning and feedback (Albayrak & Yildirim, ; Bariş & Tosun, ; Geyer, ; Karal et al, ; Miron & Ravid, ; Musa et al, ; O'Bannon, Beard, & Britt, ; O'Bannon, Britt, & Beard, ; Omar, Embi, & Yunus, ; Öztürk, ; Rachtam, Kaewkitipong, & Firpo, ; Rubrico & Hashim, ; Shih, ; Shraim, ; Souleles, ; Staines & Lauchs, ; Stankov, Glavinić, & Krpan, ; Varol, ; Vincent & Weber, ; Wang, Leng, & Lee, ).…”
Section: Formal Use Of Facebook In Formal Settings Of Learningmentioning
confidence: 98%
“…In 3% of the studies analysed the level of education was not specified. The education sector in which the largest number of studies was identified is at university level (Blair, 2013;McCarthy, 2013;Roblyer, McDaniel, Webb, Herman & Witty., 2010;Sezen, 2012;Staines & Lauchs, 2013;Tiryakioglu & Erzurum, 2011;Veletsianos & Kimmons;, although other studies were found to have been carried out at other levels of education such as secondary albeit in a minority (Doerr-Stevens, Beach & Boeser, 2011;Fardoun, Romero, Alghazzawi & Ramírez, 2012), as well as in other educational settings such as training courses (Ranieri, Manca & Fini, 2012). Other studies did not specify the level of education (Cheung, Chiu & Lee, 2011).…”
Section: Educational Level In Which Research Is Carried Outmentioning
confidence: 99%
“…In the same vein, researchers from the Pew Inter Life Project found that between 67% and 75% of college-aged young adults use social networking sites (Hew, 2011). Recent data, collected by the EDUCAUSE Centre for Applied Research (ECAR) from a sample of 36,950 students from 126 U.S. universities and one Canadian university, showed that 90% of the students use Facebook on a daily basis (Staines & Lauchs, 2013). While there is little research on the consequences of Facebook use by college students, some studies have examined the relationship between Facebook use and psychosocial outcomes.…”
Section: Introductionmentioning
confidence: 99%